2010
DOI: 10.1002/pssb.201000115
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene‐induced magnetization training effect in single molecular magnet

Abstract: Fullerene-containing complexes of Mn 12 -based single molecular magnets have been studied. It is confirmed that fullerenes have strong influence on the relaxation processes inside single molecular magnets. Notably, the hysteresis curves are found not to return to the initial point after 1 T to À1 T to1 T measurement cycle, but the magnetization progressively increases with each cycle. The effect is reproducible, and we call it ''magnetization training'' drawing an analogy with the ''magnetic training'' in exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…As we will see, the stability of magnetic deflagration is sensitive to the activation energy scaled by the energy release in the process. This ratio increases also when the active Mn 12 molecules are "diluted" with some neutral media as it was performed experimentally in, e.g., [26][27][28]. When mixed carefully with other compounds, the Mn 12 molecules retain their magnetic properties.…”
Section: A Planar Stationary Front With Incomplete Zeeman Energy Releasementioning
confidence: 79%
See 2 more Smart Citations
“…As we will see, the stability of magnetic deflagration is sensitive to the activation energy scaled by the energy release in the process. This ratio increases also when the active Mn 12 molecules are "diluted" with some neutral media as it was performed experimentally in, e.g., [26][27][28]. When mixed carefully with other compounds, the Mn 12 molecules retain their magnetic properties.…”
Section: A Planar Stationary Front With Incomplete Zeeman Energy Releasementioning
confidence: 79%
“…taking into account the perturbation modes. Thus, we have to solve the algebraic system of three equations (27), (28) and (30), taking into account the modes (25). After heavy but straightforward algebra we end up with a simple quadratic equation…”
Section: Analytical Estimates For the Pulsation Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…SMMs can also be successfully grafted onto fullerene surfaces. An example is the archetypal Mn 12 , which has been successfully grafted by cocrystallization onto C 60 fullerenes [ 187 ]. The study revealed that incorporating fullerene molecules into familiar compounds resulted in remarkable alterations in magnetization dynamics.…”
Section: Deposition Of Single-molecule Magnets On Nanostructuresmentioning
confidence: 99%
“…Let us note that a significant impact on the magnetic parameters improvement of SMMs was observed after their deposition on other carbon nanostructures. The following modifications in SMMs/nanostructure composites were reported: exceptionally high blocking temperature (around 7 K or 17 K for encapsulated Dy SMMs inside the fullerene cages [ 129 , 185 ] or even 28 K for fullerene/Tb SMMs monolayers on graphene [ 128 ]), an increase in the magnetic hysteresis (as a result of ‘magnetization training’ effect in the Mn /fullerene complex [ 187 ]), the enhancement of anisotropy barrier and relaxation times (for Tb SMMs on SWCNT [ 171 ]), and the giant magnetoresistance effect (observed in carbon nanotubes with side-attached, terbium-based SMMs [ 172 ]).…”
Section: Deposition Of Single-molecule Magnets On Nanostructuresmentioning
confidence: 99%